1991
DOI: 10.1159/000243407
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, Lipoproteins and Apolipoproteins A<sub>I</sub> A<sub>II</sub>, B, C<sub>II</sub>, C<sub>III</sub> and E in Newborns

Abstract: In this study lipid and apolipoprotein patterns were investigated at birth and compared with those of adults. In cord sera, cholesterol, triglycerides, low-density lipoprotein (LDL) cholesterol and high-density lipoprotein (HDL) cholesterol were 38.2, 46.2, 50.5, and 31.9%, respectively, of adult values. Apolipoprotein AII, B and CIII were 48.6, 30.6 and 44.5% of adult values, while apo AI, apo CII and apo E showed values approaching those of adults (63.4, 73.3 and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 18 publications
5
20
0
Order By: Relevance
“…These findings would support the possibility that a considerable proportion of fatty acids crossing the rat placenta are released to fetal circulation in their esterified form in the TAG fraction associated with specific lipoproteins. The pattern of lipoproteins in fetal circulation differs from that in adults, as it has been shown in both rats (2) and humans (3,4,40). This suggestion is consistent with the report that rat yolk sac can synthesize apolipoprotein B (apo B)-containing lipoproteins (41) and that the placenta can express apo-B (8); similar findings have also been reported in mouse yolk sac (12,44) and in the human placenta (35).…”
Section: Nssupporting
confidence: 85%
See 1 more Smart Citation
“…These findings would support the possibility that a considerable proportion of fatty acids crossing the rat placenta are released to fetal circulation in their esterified form in the TAG fraction associated with specific lipoproteins. The pattern of lipoproteins in fetal circulation differs from that in adults, as it has been shown in both rats (2) and humans (3,4,40). This suggestion is consistent with the report that rat yolk sac can synthesize apolipoprotein B (apo B)-containing lipoproteins (41) and that the placenta can express apo-B (8); similar findings have also been reported in mouse yolk sac (12,44) and in the human placenta (35).…”
Section: Nssupporting
confidence: 85%
“…*Corrected as explained in the text. Different superscripted lowercase letters indicate significant differences between hours for a specific fatty acid, for which its ANOVA P value is shown by p 2 ; different superscripted uppercase letters indicate significant differences between radioactive fatty acids at the same time, for which its ANOVA P value is shown by p 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite this variation, the TC, TG, and lipoproteins levels in the cord blood are lower than in adults and the relative proportion present in HDL-C as opposed to LDL-C is much higher (24)(25)(26)(27)(28). Evidence has shown that the maternal lipid levels are affected by maternal factors such as BMI, maternal weight gain, diet, pre-pregnancy lipid levels, parity, mode of delivery and various medical complications of pregnancy that may have significant impacts on lipid metabolism and plasma levels (13,14,17,23,29,30).…”
Section: Discussionmentioning
confidence: 98%
“…The apo AI levels increase in plasma after a fatty meal. A postnatal increase of apo AI has been observed previously in healthy enterally fed term and preterm infants [8,10,[26][27][28][29]. Apo AI as a cofactor of LCAT is essential for metabolizing intravenous lipid emulsion constituents, but the level of this enzyme is very low in parenterally fed preterm infants [10,29,30].…”
Section: Discussionmentioning
confidence: 89%
“…Parker et al [23] described an influence of gestational age on apo AI, but found a positive correlation with increasing levels only between 21 and 32 weeks of gestation. The overall cord blood apo AI levels are approximately 60-70% of those of adults [26,27]. The apo AI levels increase in plasma after a fatty meal.…”
Section: Discussionmentioning
confidence: 96%